How to minimize air embolisms during thoracic endovascular aortic repair with Relay Pro?. (13th November 2019) - Rylski, Bartosz; Mayer, Florian; Beyersdorf, Friedhelm; Kondov, Stoyan; Kolowca, Maciej; Kreibich, Maximilian; Czerny, Martin
Abstract: The aim of this study was to evaluate the volume of air released from Relay Pro NBS thoracic stent grafts using different de-airing methods. The gas volume was measured in an in vitro experimental setting. Stent grafts were de-aired via (i) standard saline flushing (40 ml), (ii) increased volume saline flushing (120 ml), (iii) carbon dioxide followed by 40 ml saline flushing and (iv) de-airing with 40 ml of saline in an ultrasound bath. The volume of gas released was measured separately while introducing the folded stent graft in the delivery device into the simulated aorta (step 1) and while deploying it outside the delivery device (step 2). Median air volumes released during steps 1 and 2 after flushing with 40 ml of saline were 0.09 (1st–3rd quartile 0.06–0.21) and 0.14 (0.11–0.15) ml, respectively. The volume of air released during step 2 was significantly less [0.09 (0.08–0.10) ml] after de-airing with 120 ml saline ( P  = 0.049). Neither de-airing with carbon dioxide nor in an ultrasonic bath led to a reduction in the volume of gas released during step 2. Air remaining after de-airing with a standard 40 ml of saline was released partially during stent graft introduction into the aorta and partially during final deployment. The most effective method of reducing air volume was de-airing with increased saline volume.